Molecular sexing in Bos taurus using quantitative polymerase chain reaction (qPCR) method - Fathurrahman, I.; Kusumawati, A.; Rahman, A.; Ulviani, Y.; Prihantoko, K.D.; Unsunnidhal, L. (IOP Publishing Ltd, 2022)
Cattle are animals that are widely found all over the world which is the domestication of bulls. In Indonesia, domesticated cattle are used as livestock, could be meat cattle or dairy cattle. The sex of the cattle is very influential in terms of selling, especially the type of bull. Calf bull is a product of the process of artificial insemination with spermatozoa resulting in sexing. Mammals have X and Y chromosomes to distinguish their sex. Each chromosome has a special gene such as the SRY gene on the Y chromosome and the PLP gene on the X chromosome. Molecular methods are effective methods of determining the chromosomes carried by spermatozoa. Both special genes are found in the home box (GADPH) of mammals. Primer is made from the mRNA SRY (sex-determining region Y) sequence from Bos taurus with a size above 200bp (SRY B) and below 200bp (SRY A) so that optimal results are obtained between the two. The type of sample that has been used in this research was sexing semen from limousin bulls that are treated from 4 pairs of primers each. The results of the qPCR from both primers are viewed from the melt-peak graph and comparison analysis. The differences between SRY A and SRY-B primer indicates that SRY-A produces a more stable melt-peak graph than SRY B. This indicates that the SRY A primer is more stable when used for molecular verification processes using qPCR. © Published under licence by IOP Publishing Ltd.